Conservation management plan involving local community - Kong, Wai Ling (Universiti Malaysia Sarawak, (UNIMAS), 2009)
CForested lands are often managed by developers for the production of timber. However, conventional logging was often practiced to minimize cost and time, and at the same time, maximize profit. Poor management has led to the destruction of the forest ecosystem, effecting its natural regeneration, wildlife and the community, whose livelihood depends o) Therefore, this study will focus on proper community forestry, where not only the economical value are beneficial to the developer, but also to the community, in addition to the cultural, spiritual, social, medicinal, ecological, recreational and aesthetic values. Primary data were obtained through experimental research, whereby sample plots were set up to determine tree species and flora diversity, and lines transect sampling to estimate the population of mammals and birds. Fish population was studied through the establishment of several sampling stations. Nearby community were interviewed on their experiences and perception on development of the study area. Secondary data such as satellite images and topography maps were used to carry out forest mapping. Quantitative results show the coverage of the study area, and its proposed three (3) different uses; namely community use (36.68%), water catchment area (32.26%) and conservation area (31.00%). The forest resource assessment reveals that the average stocking of the study area for trees exceeding 20cm DBH, is approximately 111.50/ha., thus making the area a potential for commercial stock stands. The study area also consists several non-timber forest resources such as bamboo, rattan, palms, wild gingers, ferns and wild bananas. On wildlife study, 42 mammal species (11 protected), 172 bird species (8 totally protected, 31 protected) and 23 fish species were identified. Community study reveals that the majority were of the Penan and Kayan community. Their income came from the selling of crafts as well as agriculture and jungle products. They, however, lack essential facilities, such as power and clean water supply. A theoretical analysis, backed by experimental studies and observations, indicates that a proper forest management plan will play an important part of rehabilitation and conservation of the study area, and also development to the rural communities.